The process of harmonization of accounting in the Czech Republic - Honková, Irena (Masarykova univerzita, 2016)
The article was written in response to the amendment to Decree No. 250/2015 Coll., which came into effect from January 1, 2016. This amendment shows the harmonization of the Czech accounting system with the International Financial Reporting Standards (IFRS), e.g. in reporting of extraordinary income and expenses, of formation expenses, or in valuation of inventory produced internally. Consequently, a survey has been conducted, in which 24 persons having experience with the accounting under the IAS/IFRS commented on how they coped with the differences between the Czech Accounting Standards (CAS) and the IAS/IFRS. It has been found that these companies normally keep the accounts simultaneously in both systems (CAS and IAS/IFRS). However, some companies decided to keep the accounts only in one accounting system, supplemented with the differences between the two systems. It is undisputed that the process of harmonization of accounting systems continues. However, the final unification of our national system with the European one has not happened so far. There is a need to harmonize accounting and tax regulations as well.
Proces harmonizace účetnictví v České republice
Keywords: International Financial Reporting Standards (IFRS); Czech accounting standards (CAS); harmonization of accounting.; Mezinárodní standardy finančního výkaznictví (IFRS); České účetní standardy (ČÚS); harmonizace účetnictví.